Do screening ao mecanismo de ação, uma contribuição para a descoberta de ciclopaladados bioativos: a atividade leishmanicida de CP2 e seu efeito inibitório frente à DNA topoisomerase 1B de Leishmania - Velásquez, Angela Maria Arenas [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Leishmaniasis are diseases globally distributed in tropical and subtropical areas of the world and Leishmania spp. are the etiological agents of the diseases. Numerous problems associated with available treatments of the disease are still unsatisfactory because currently available drugs are highly toxic, little effectiveness and drug resistance cases have emerged. Furthermore, leishmaniasis are a neglected disease by pharmaceutical industries and governments. In the search for new drugs with a broad spectrum of action and low toxicity, there is evidence to suggest that transition metal complexes can act in several compartments or organelles of protozoa, as well as to present low toxicity in the mammalian host. In this work, we evaluated the leishmanicidal and trypanocidal in vitro activity of six cyclopalladated compounds: [Pd(dmba)(µ-Cl)]2 (CP1), [Pd(dmba)(µ-N3)]2 (CP2), [Pd(dmba)(µ-NCO)]2 (CP3), [Pd(dmba)Cl(isn)] (CP4), [Pd(dmba)(N3)(isn)] (CP5), [Pd(dmba)(NCO)(isn)] (CP6) and the free ligands, Hdmba: N,N- dimethylbenzylamine e isn: isonicotinamide. The cyclopalladated complexes CP2 inhibited the growth of the promastigote forms of Leishmania amazonensis (IC50 = 13,2 ± 0,7 µM), reduced the proliferation of intracellular amastigote forms (IC50 = 10,2 ± 2,2 µM) and showed a low cytotoxic effect against peritoneal macrophages (CC50 = 506,0 ± 10,7 µM). In vitro assays against T. cruzi and T. brucei, parasites that cause Chagas disease and sleeping sickness, respectively, demonstrated that cyclopaladate compounds have a wide spectrum of action and constitute an excellents candidates for the treatment of these neglected diseases. CP2 was at least fifty-times more selective for intracellular amastigote forms of L. amazonensis and two hundred-times more selective for intracellular amastigote forms of T. cruzi vs. mammaliam cells. For in vivo assays, CP2 (0.35 mg/Kg/day) was not toxic to BALB / c mouse infected with L. amazonensis, no changes were observed in biochemical markers of renal/hepatic function, in in silico studies showed a 100% of permeability for intestinal absorption and the parasite load of the animals was reduced to 80%, like amphotericin B (2 mg/Kg in alternate days), the drug currently used in the leishmaniasis treatment. In-depth studies of the mechanism of action have shown that CP2 can inhibit the cleavage step of Leishmania DNA Topoisomerase 1B. Comparative proteomic analysis (two-dimensional electrophoresis, followed by mass spectrometry) were performed to identify proteins differentially expressed in L. amazonensis in the absence / presence of CP2 and thus to determine molecular events generated from the inhibition of parasite DNA Topoisomerase. We found in the proteomic analysis chaperonins associated with different stresses (calreticulin, putative 10 kDa heat shock protein, putative heat-shock protein hsp70, putative glucose-regulated protein 78, protein disulfide-isomerase), proteins that act in the process of cellular detoxification (trypanothione reductase, peroxidoxin, tryparedoxin peroxidase) and other proteins associated with several biological processes associated with a possible programmed cell death in Leishmania.

As leishmanioses são doenças mundialmente distribuídas, encontradas nas áreas tropicais e subtropicais do mundo e que são caudas por protozoários parasitos do gênero Leishmania spp. A pesar dos inúmeros problemas associados aos tratamentos disponíveis (como alta toxicidade dos fármacos, limitada eficácia e casos de resistência haverem surgido), ainda estás doenças são negligenciadas pelas industrias farmacêuticas e pelos governos. Na procura por novos fármacos com amplo espectro de ação e baixa toxicidade, há evidências que sugerem que complexos de metais de transição podem atuar em diversos compartimentos ou organelas dos protozoários, além de apresentar baixa toxicidade no hospedeiro mamífero. No presente trabalho, realizou-se a avaliação leishmanicida in vitro de seis compostos ciclopaladados, [Pd(dmba)(µ-Cl)]2 (CP1), [Pd(dmba)(µ-N3)]2 (CP2), [Pd(dmba)(µ-NCO)]2 (CP3), [Pd(dmba)Cl(isn)] (CP4), [Pd(dmba)(N3)(isn)] (CP5) e [Pd(dmba)(NCO)(isn)] (CP6) e seus correspondentes ligantes livres, Hdmba: N,N-dimetilbenzilamina e isn: isonicotinamida. O composto CP2 inibiou o crescimento das formas promastigotas de Leishmania amazonensis (IC50 = 13,2 ± 0,7 µM), reduz a proliferação das formas amastigotas intracelulares (IC50 = 10,2 ± 2,2 µM) e apresentou um baixo efeito citotóxico frente a macrófagos peritoneais (CC50 = 506,0 ± 10,7 µM). Dados in vitro da atividade anti-T. cruzi e anti-T. brucei, parasitos causadores das doenças de Chagas e do sono, respectivamente, também demonstraram que os compostos ciclopaladados apresentam amplo espectro de ação constituindo-se em excelentes candidatos para o tratamento das doenças negligenciadas em estudo. O composto CP2 apresentou-se para as formas amastigotas intracelulares de L. amazonensis pelo menos 50 vezes mais seletivo e 200 vezes mais seletivo para as amastigotas de T. cruzi vs. células de mamífero. Em estudos in vivo, utilizando o modelo BALB/c infectado com L. amazonensis, CP2 (0,35 mg/Kg/dia) não apresentou toxicidade, quando investigados marcadores bioquímicos de função renal e hepática, em estudos in silico mostrou uma permeabilidade de 100% para absorção intestinal, e reduziu em 80% a carga parasitária dos animais, resultado promissor e comparável à anfotericina B (2 mg/Kg em dias alternados), fármaco atualmente utilizado no tratamento das leishmanioses. Diante das potencialidades deste composto em estudos aprofundados do mecanismo de ação mostrou-se que CP2 é capaz de inibir a etapa de clivagem da DNA Topoisomerase 1B de Leishmania. Análise proteômica comparativa (eletroforese bidimensional, seguida por espectrometria de massas) foram realizadas para identificar proteínas diferencialmente expressas em L. amazonensis na ausência/ presença de CP2 e assim determinar os eventos moleculares gerados em cascata a partir da inibição da DNA Topoisomerase do parasito. Dentre as proteínas encontradas nos ensaios supracitados, destacam-se chaperoninas associadas à diferentes estresses (calreticulina, proteína de choque térmico 10KDa -HSP10-, HSP70, GRP78 e dissulfureto isomerase), proteínas que atuam no processo de detoxificação celular (tripanotiona reductase, peroxiredoxina, triparedoxina peroxidase) e outras proteínas associadas com diversos processos biológicos que podem estar relacionados com o processo de Morte Celular Programada em Leishmania.
From screening to mechanism of action, a contribution to the discovery of bioactive cyclopalladated: the leishmanicidal activity of CP2 and its inhibitory effect against Leishmania DNA topoisomerase 1B
Keywords: Leishmanioses; Doença de Chagas; Leishmania amazonensis; Trypanosoma cruzi; DNA topoisomerase 1B; Complexo ciclopaladado; Leishmaniasis; Chagas disease; Cyclopalladated compounds